An example of calculating time, speed and brake way of the car on the site of the second braking position at the hump yard under the influence of small crosswinds - K. T. Turanov; A. A. Gordienko (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
To present day the speed of sliding car in the theory of calculation of marshaling hump determined by the formula of free falling body, where the acceleration of free falling bodies are given with the inertia of the wheelsets, which is unacceptable. Therefore, for the first time the movement of the car on the part of the second hump brake position of marshaling hump under the influence of the small crosswinds was studied. Force relations that take place in the system “car-railway track” on the second hump brake position under the influence of the cross-wind of the small value was given. These force relations include “shifting” (i.e. the projection of the gravity of the car with load and cross-wind on the direction of movement of the car) and “restraining” forces. By the difference between “shifting” and “restraining” forces and weight of the car without inertia of the rotating parts (wheel pairs) and with using the basic law of dynamics of a body with non-ideal constraints (D’Alembert’ principle), acceleration of the car when driving in the second hump brake position under the influence of the cross-wind was calculated. Then, the braking time and the sliding speed of the car related to rail lines and braking tires of car retarders is determined by the classical formula for the track and speed of uniformly decelerated motion. On this basis, for the first time results of researching of car movement with acceleration in the second hump braking position is given. Graphic dependences of speed and the way of the car braking from the time of movement were built. By combining built graphic dependences rational time values of sliding speed and the braking way of the car were found. Presented results of researches can be used in the calculation of the motion time and speed of sliding of the car on the next parts of the hump, and in the future to complete development of the corrected program of calculation of the lowering part of a hump from its top to the estimated point.